THE ANALYSIS OF CONTENT CHARACTERISTICS ON INSTAGRAM IN THE F&B GREEN TEA INDUSTRY IN JAPAN - Mahdaria, Siti; Putra, Raditya Pratama (Laboratorium Ilmu Komunikasi Fisip UHO, 2024)
The popularity of green tea across the globe has brought many foreign visitors to visit Japan, the country where green tea culture develop. It encourages the growth of the green tea business in Japan which led to the high competition in the Japanese green tea industry. Two brands of Green Tea Farms that are popular among tourists include D:matcha Kyoto and Obubu Tea Farms. This paper aims to analyse the content characteristics of Instagram to find out what type of content earns the highest engagement rate in the Green Tea industry in Wazuka, Japan. The data will be collected from social media analytical tools FanPaga Karma, and will be analysed using The Circular Model of SoMe for problem identification for content distribution. The research approach is descriptive analysis. The research found that the type of content on Instagram that mostly earned a high interaction rate from the audience of the F & B green tea industry in Japan are reels and carousels with the theme of human interest and product focus. This study contributes to the understanding of effective content to promote green tea business on Instagram.